Downward nominal wage rigidity meets the zero lower bound - Robert A. Amano; Stefano Gnocchi (Bank of Canada, 2017)
We add downward nominal wage rigidity to a standard New Keynesian model with sticky prices and wages, where the zero lower bound on nominal interest rates is allowed to bind. We find that wage rigidity not only reduces the frequency of zero bound episodes but also mitigates the severity of corresponding recessions. As a result, previous studies abstracting from the presence of wage rigidity may have overemphasized the need for increasing the inflation target to offset the costs associated with hitting the zero bound. Moreover, our findings add to the recent debate on the presumed benefits of wage flexibility that has arisen in the aftermath of the Great Recession.
Keywords: E24; E32; E52; 330; Monetary policy framework; Inflation targets; Labour markets